Ozempic: the gold standard for weight normalisation or a “lifeboat” - Salivon, Hanna; Klymenko, Olena (The Ukrainian Scientific Medical Youth Journal, 2026)
obesity, type 2 diabetes mellitus (T2DM), and metabolic syndrome remain prevalent global health challenges requiring comprehensive management strategies. Semaglutide, a glucagon-like peptide-1 receptor agonist (GLP-1RA), has emerged as a significant pharmacological intervention. The study aims to analyze current scientific data to critically assess the clinical efficacy and safety of semaglutide (Ozempic) in treating T2DM and obesity, determining its position in modern therapeutic protocols. A descriptive review of the literature was conducted, analyzing key phase III clinical trials, including the SUSTAIN, PIONEER, STEP, and SELECT programmes. The review focuses on pharmacokinetic properties, glycaemic control, weight loss outcomes, and cardiovascular safety profiles of both subcutaneous and oral semaglutide formulations. Clinical trials demonstrate that semaglutide significantly reduces glycated haemoglobin (HbA1c) by -1.0% to -1.8% and induces substantial weight loss(averaging 15%), surpassing earlier GLP-1RAs. The drug exhibits pleiotropic effects, including improved endothelial function and reduced inflammation, contributing to cardiovascular protection, with a relative reduction of major adverse cardiovascular events (MACE) by 20%. However, rapid weight regains upon discontinuation and potential adverse effects such as gastrointestinal disturbances remain significant concerns. Semaglutide represents a highly effective pharmacological option for managing metabolic disorders, offering benefits beyond glycaemic control. While it sets a high standard for efficacy, issues regarding cost, accessibility, and the necessity for long-term adherence categorize it as a specialized resource requiring strategic implementation rather than a universally accessible cure.